Mucosal and lacrimal flaps for endonasal dacryocystorhinostomy: a systematic review. (13th October 2016) - Green, R.; Gohil, R.; Ross, P.
Abstract : Background: Historically dacryocystorhinostomy (DCR) has been performed externally with very good outcomes. Current literature shows comparable success rates between endonasal and external approaches. A common reason for the failure of a DCR is the reclosure of the nasolacrimal stoma by granulation tissue and synechiae. Objective of review: A systematic review and critical evaluation of the evidence relating to the preservation of nasal mucosal flaps in DCR surgery. Type of review and evaluation method: A systematic review using the consort guidance for review of randomised control trials. Search strategy: A search of the following evidence‐based medicine databases was performed: Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effectiveness, Cochrane Central Register of Controlled Trials, Ovid, Medline, EMBASE and PubMed. The search was limited to English language articles, and the following key words were used: Endonasal, Endoscopic, Dacryocystorhinostomy, DCR, Mucosal Flaps, between years 1970 and 2015. Results: The best available evidence was level 1B, comprising two randomised control trials and three comparative studies included in the review. The main outcome measures used were lacrimal irrigation and absence of epiphora. Two of the studies demonstrated a statistically significant benefit of mucosal sparing either with nasal mucosal flaps or with lacrimal flaps. More debridement was needed, and granulation tissue was also seen in the groups without mucosal preservation. There was no difference in surgical complications between a mucosal and non‐mucosal‐sparing technique. Conclusions: The overall quality of current evidence is poor, and there does however appear to be a trend towards improved outcomes and reduced granulation in groups where nasal mucosal and lacrimal flaps were preserved, but this is not clear‐cut. There was no evidence of increased complication rates with mucosal‐sparing techniques. We recommend that until further good quality research is available we should be performing a mucosal‐sparing technique when performing DCR routinely.